Election Outcomes and Individual Subjective Wellbeing in Great Britain. (16th February 2021) - Gray, Daniel; Pickard, Harry; Munford, Luke
Abstract : Exploiting novel longitudinal data on individuals in Great Britain matched to their parliamentary constituency, we find that supporting the incumbent political party, at both the national and constituency levels, exerts a positive influence on individual subjective wellbeing. This relationship varies across different measures of subjective wellbeing, gender and personal characteristics. We then implement a regression discontinuity in time design to estimate the impact of a quasi‐natural experiment, where we exploit the timing of the survey around the 2010 election date in order to identify a causal relationship. We find that Liberal Democrat supporters have approximately one‐unit higher level of overall life satisfaction after their party's electoral success.